Sosialisasi Bentuk Latihan Small Side Game dalam Permainan Sepak Bola di SMP se Kecamatan Kampar - Rizky, Elfera (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The Socialization of Small-Sided Game Training in Football at Junior High Schools Across Kampar District" aims to introduce a modified training method that limits the number of players, field size, and duration. This type of training also helps improve skills such as passing, dribbling, and decision-making under pressure. Small-sided games are football training sessions conducted on smaller fields with fewer players than the standard 11-a-side game. The implementation of this training can be adapted to various age groups, including young players. Through small-sided game training, children can enhance their passing skills and teamwork.